2013
DOI: 10.1124/dmd.112.050344
|View full text |Cite
|
Sign up to set email alerts
|

Drug Transporters on Arachnoid Barrier Cells Contribute to the Blood–Cerebrospinal Fluid Barrier

Abstract: The subarachnoid space, where cerebrospinal fluid (CSF) flows over the brain and spinal cord, is lined on one side by arachnoid barrier (AB) cells that form part of the blood-CSF barrier. However, despite the fact that drugs are administered into the CSF and CSF drug concentrations are used as a surrogate for brain drug concentration following systemic drug administration, the tightjunctioned AB cells have never been examined for whether they express drug transporters that would influence CSF and central nervo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
119
3
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(124 citation statements)
references
References 32 publications
0
119
3
2
Order By: Relevance
“…It is well recognized that P-gp may protect the brain from noxious substances [22]. Within the CNS, this transporter is located at the apical membranes of the blood-CNS barriers, adluminal to the blood at the (BBB, brain endothelial cells) [17] and the arachnoid barrier cells at the arachnoidea mater [23] as well as adluminal to the CSF at the blood CSF barrier (BCSFB, epithelial cells of the choroid plexus) [17]. The relative distribution and functionality of P-gp at the 3 barriers is unclear in humans.…”
Section: Resultsmentioning
confidence: 99%
“…It is well recognized that P-gp may protect the brain from noxious substances [22]. Within the CNS, this transporter is located at the apical membranes of the blood-CNS barriers, adluminal to the blood at the (BBB, brain endothelial cells) [17] and the arachnoid barrier cells at the arachnoidea mater [23] as well as adluminal to the CSF at the blood CSF barrier (BCSFB, epithelial cells of the choroid plexus) [17]. The relative distribution and functionality of P-gp at the 3 barriers is unclear in humans.…”
Section: Resultsmentioning
confidence: 99%
“…34) In addition to these reports, Yasuda et al have found that arachnoid barrier epithelial cells, which are present in meninges, express several kinds of transporters, such as P-glycoprotein and ATPbinding cassette transporter G2. 35) Thus, there is a possibility that these epithelial cells also involves in vivo spermine elimination from the CSF. Further studies involving identification of spermine-recognizing transporters which are distinct from well-known transporters and the expression of these molecules on choroid plexus epithelial cells, ependymal cells, and arachnoid barrier epithelial cells, may help us to better understand the details of this spermine elimination from the CSF.…”
Section: Resultsmentioning
confidence: 99%
“…There are many differences between the transporters and enzymes expressed in the different barrier layers, suggesting that they play different but complementary roles in regulation of molecular fl ux (Strazielle and Ghersi-Egea 2013 ;Saunders et al 2013 ;Yasuda et al 2013 ). The transporters present include considerable overlap in function/apparent redundancy at each site, refl ecting their evolutionary history (Dean and Annilo 2005 ) and ensuring maintained function in case of loss or defect of a single transporter.…”
Section: Small Solute Transport At the Barrier Layersmentioning
confidence: 99%